Complete root coverage in the treatment of Miller class III or RT2 gingival recessions: a systematic review and meta-analysis - Aitziber Fernández-Jiménez; Ana-María; Ruth Estefanía-Fresco; Xabier Marichalar-Mendia; José-Manuel A; Luis-Antonio A (BMC, 2021)
Abstract Background The primary objective of this systematic review and meta-analysis was to assess the evidence on complete root coverage (CRC) achieved by periodontal plastic techniques in the treatment of Miller class III/RT2 gingival recessions, comparing techniques developed along the twentieth century (pre-twenty-first) versus surgical approaches of the twenty-first century (21st). Methods An electronic bibliographic search was carried out in four databases up to December 2019, focusing on studies that reported CRC results in Miller class III or RT2 recessions treatment with at least a six-month follow-up. In addition, a random-effects models' meta-analysis was performed for the CRC, comparing pre-twenty-first versus twenty-first century techniques at 6 months, 12 months and more than 12 months. Results Thirty-seven publications were included. A total of 933 gingival recessions were treated, 298 with pre-twenty-first century surgical techniques and 635 with techniques from the twenty-first century. CRC was achieved at 6 months on half of the recessions (pre-twenty-first: 57.60% vs. 21st: 51.11%), but decreased markedly for twenty-first century techniques at 12 months (pre-twenty-first: 63.82% vs. 21st: 32.87%). Thereafter, this difference was the other way around (> 12 months: pre-twenty-first: 5.26% vs. 21st: 19.65%). The meta-analysis showed a high heterogeneity, with no significant differences amongst the techniques. Conclusions Although CRC might be achievable by treating Miller class III or RT2 recessions with any of the described techniques, its long-term stability is not predictable. More randomized clinical trials with longer follow-ups and several visits, are needed. In addition, the patient's satisfaction should also be assessed.